PENGAWASAN PENYELENGGARAAN PELAYANAN PUBLIK DALAM PEMERINTAH DESA - Fatkhurohman Fatkhurohman (Universitas Widya Gama Malang, 2018)
Public service is part of social basic to the citizens/ it is through public service that the government do its responsibility to meet needs and to try to improve its peoples prosperity. One of the facilities is to improve public service to villagers through a regulation on village namely the 2014 law No. 6 on village, stating that the regulation on villages is intended to improve the public service for villagers to accelerate the realization of a public prosperity. This article is intended to discuss the mechanism in giving public services in village government. Based on the normative method, it can be concluded that the supervision of public service in village government was not explicitly stated. This supervision should be made to prevent any misuses of authority. Kata Kunci: pelayanan publik, pemerintahan desa, penyalahgunaan wewenang.